Molecular epidemiology of dengue fever outbreaks in Bhutan, 2016-2017. - Sangay Zangmo; Jit Bdr Darnal; Tsheten; Sonam Gyeltshen; Binay Thapa Thapa; Prinyada Rodpradit; Piyawan Chinnawirotpisan; Wudtichai Manasatienkij; Louis R Macareo; Stefan Fernandez; Sonam Wangchuk; Chonticha Klungthong (Public Library of Science (PLoS), 2020)
Dengue continues to pose a significant public health problem in tropical and subtropical countries. In Bhutan, first outbreak of dengue fever (DF) was reported in 2004 in a southern border town, followed by sporadic cases over the years. In this study, we analysed DF outbreaks that occurred in 3 different places during the years 2016 and 2017. A total of 533 cases in 2016 and 163 in 2017 were suspected of having of DF, where young adults were mostly affected. A total of 240 acute serum specimens collected and analyzed for serotype by nested RT-PCR revealed predominance of serotypes 1 and 2 (DENV-1 and 2). Phylogenetic analysis using envelope gene for both the serotypes demonstrated cosmopolitan genotype which were closely related to strains from India, indicating that they were probably imported from the neighboring country over the past few years.